Directory of on-going research in cancer epidemiology. - International Cancer Research Data Bank.; Deutsches Krebsforschungszentrum Heidelberg; International Agency for Research on Cancer (Lyon : IARC, 1977)
908 numbered entries to projects in 70 countries. Contents reveal i ncreasing interest in specific industrial exposures and consequences to health. Geographical arrangement. Entry gives identification of proj ect and investigator, description of project, indexing terms, anatomica l sites studied, location where work is being done, and time period for conducting study. Indexes for subjects, investigators, geographical l ocations, anatomical sites, and study types (e.g., autopsy,biopsy, hosp ital records). Also contains list of Population-based cancer registrie s.
Vols. for 1977-78, 1980- issued as IARC scientific publication ; no. 17, etc.; for 1979, as IARC publication ; no. 28.
Previous ed. not issued in the IARC scientific publications series.
A joint effort of the International Agency for Research on Cancer an d the German Cancer Research Center, within the framework of the Intern ational Cancer Research Data Bank Program of the National Cancer Instit ute of the United States.
Keywords: Epidemiology; Neoplasms -- directory; Research